Pengaruh Motivasi, Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan di Kemantren Pakualaman - Fajri Anggita Putri; Jumadi Jumadi (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of motivation, work discipline, and work environment on employee performance at the Pakualaman Kemantren Office. Respondents in this study were 47 people and the entire population was used as research. The research method used in this research is quantitative method, data collection using a questionnaire with a Likert scale. Analysis using descriptive analysis, multiple linear regression analysis and hypothesis testing. The results showed that based on the t test, it is known that the motivation variable partially does not have a significant effect on employee performance at Kemantren Pakualaman. While the work discipline and work environment variables based on the t test partially have a significant effect on employee performance at Kemantren Pakualaman. Based on the f test, it shows that the variables of motivation, work discipline, and work environment together have a significant effect on employee performance variables at Kemantren Pakualaman. Based on these results, it can be concluded that improving employee performance is more influenced by discipline and good working environment conditions, compared to individual motivational factors.